2022
DOI: 10.2147/ijn.s344208
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Nanoparticle Delivery to Tumors Using Machine Learning and Artificial Intelligence Approaches

Abstract: Background Low delivery efficiency of nanoparticles (NPs) to the tumor is a critical barrier in the field of cancer nanomedicine. Strategies on how to improve NP tumor delivery efficiency remain to be determined. Methods This study analyzed the roles of NP physicochemical properties, tumor models, and cancer types in NP tumor delivery efficiency using multiple machine learning and artificial intelligence methods, using data from a recently published Nano-Tumor Database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…Previous studies have suggested that the tumor size is related to the EPR magnitude of tumors, which is revealed in our models as the positive relationship between delivery efficacy and tumor weight. [13] The tumor type was reported as another important determinant in predicting delivery efficacy, [10,13] which is also confirmed by the importance of genomic profile in our models. Because there is strong multicollinearity between tumor types/lineages and the genomic profiles, we excluded the tumor types/lineages from the model construction to increase the reliability of the statistical inferences.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Previous studies have suggested that the tumor size is related to the EPR magnitude of tumors, which is revealed in our models as the positive relationship between delivery efficacy and tumor weight. [13] The tumor type was reported as another important determinant in predicting delivery efficacy, [10,13] which is also confirmed by the importance of genomic profile in our models. Because there is strong multicollinearity between tumor types/lineages and the genomic profiles, we excluded the tumor types/lineages from the model construction to increase the reliability of the statistical inferences.…”
Section: Discussionsupporting
confidence: 81%
“…The delivery efficacy dataset was obtained from the previously published meta-analysis, [10] containing the delivery efficacy at 24 h (DE24), 168 h (DE168), and the maximum delivery efficacy (DEmax) after intravenous injection of NPs. The original dataset contains 330 samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventh, the present model is in healthy rats, and thus cannot be used to predict delivery efficiency of AuNPs to tumor. However, the present model provides a basis to be extrapolated to tumor-bearing animals by adding a tumor compartment to help address low tumor delivery efficiency issue [4,52]. Finally, the model does not include the lymphatic system due to the lack of pharmacokinetic data of AuNPs in lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Since the rapid progress of computational facilities, artificial intelligence using machine learning (ML) has developed rapidly and has been used in some of the research areas in the medical field, including cancer, cardiovascular disease, neurological disease, emergency medicine and even in the pharmacological field, etc. [ 17 , 18 , 19 , 20 , 21 ]. The definition of ML is the study of computer algorithms that can improve automatically through experience and by the use of data [ 22 ].…”
Section: Introductionmentioning
confidence: 99%